Mobile Applications and Communications Strategies for Environmental Non-Governmental Organizations - Denis VASILIEV (Communications of International Proceedings, 2021)
Mobile applications are becoming increasingly popular in modern marketing communications. Businesses successfully harness the power of new media for multiple purpose, including e-commerce, marketing research, relationship management, marketing, public relations and many more. Mobile applications have a great potential for use not only in business sector but also in non-governmental, governmental, and scientific organizations. Environmental non-governmental organizations (ENGOs) usually have sophisticated communications strategies often requiring both general public engagement and interactions with specific stakeholder groups. The organizations often also engage in scientific work. Mobile applications may facilitate all these tasks and, therefore, form an important part of communications mix for ENGOs. To find out to what extent the ENGOs harness this opportunity research was conducted examining presence and use cases of Android mobile applications by global and European ENGOs. It was found that uses of the applications are limited both among ENGOs operating internationally and locally. This is a significant shortcoming, which needs to be addressed. In order to provide recommendations for the ENGOs, uses of the applications are critically evaluated, providing suggestion that could facilitate right technology choices for the ENGOs. Also, different technological frameworks used for application development are discussed, proposing most cost-effective and powerful solutions.
Keywords: Mobile Marketing; Communications Strategies; Citizen Science; Machine Learning.